AN INVESTIGATION ON RISK FACTORS RELATING TO THE TREATMENT DIFFICULTY IN ORIGINALLY TREATED PULMONARY TUBERCULOSIS CASES - KAJIKI, Akira; HARADA, Susum; IKEDA, Akihito; KITAHARA, Yoshinari; HARADA, Yasuko; TAKAMOTO, Masahiro; MARUYAMA, Masao; ISHIBASHI, Tuneo (Kekkaku, 1994)
In order to investigate whether so-called risk factors relating to treatment difficulty are true risk or not, treatment results of 520 in-patients originally treated for pulmonary tuberculosis during 12 years' period from 1980 to 1991 in our hospital were analyzed. The proportion of cases with so-called risk factors among total 520 cases was as follows: Aged patients (70 years of age and over) 31.5% Cases discharging abundant bacilli in sputum (Gaffky scale VII or above or culture positive) 29.4% Adverse reactions to drugs 18.1 % Far advanced cavitary lesions (GAKKAI Classification I or II3) 15.6% Relative risk of various risk factors in cases of group A (died of tuberculosis), group B (showed delay in the negative conversion of bacilli; namely, cases converted to negative only 4th month of treatment or later) and group C (cases of groups A and B) were calculated comparing with cases of the control group (pretreatment negative bacilli cases or cases converted to negative within 3 months). In cases of group A died of tuberculosis, the results were as follows; pretreatment abundant bacilli discharge 3.1, far advanced cavitary lesions 4.6, emaciation and/or malnutrition 5.1. Other risk factors identified were the following; unhealthy life style 4.0, severe gastrointestinal tract disease 3.9, impaired pulmonary function 3.3, complicated infections 3.2, cerebrovascular injuries including psychosis and nervous system diseases 2.3, diabetes mellitus 2.0, and the adverse reactions to drugs 1.9. In cases of group B showing delay in the negative conversion of bacilli, significant risk factors were pretreatment abundant bacilli discharge, far advanced cavitary lesions, emaciation and/or malnutrition and diabetes mellitus. The prevalence of risk factors was compared between aged cases (70 years of age and over) and the control (less than 70 years of age). The severity of the disease was similar in both groups, however, the prevalence of cases with complicated infections, emaciation and/or manutrition, malignancies, silicosis, impaired pulmonary function and cere brovascular injuries was significantly higher in the aged cases. The higher age was regarded as one of risk factors relating treatment difficulty, as several risk factors mentioned above were found more frequently in the aged patients.